A STUDY ON PROBLEMS FACED BY THE SELF HELP GROUP MEMBERS WHILE AVAILING FINANCIAL BENEFITS THROUGH SELF HELP GROUP BANK LINKAGE PROGRAMME IN SIVAKASI (CAHIERS MAGELLANES-NS, 2024)
Since the evolution of Self help groups, even there is a lot of improvements in the strategies use by the banks with the guidance of Government of India, there is the existence of certain problems in receiving financial benefits through SHG bank linkage programme. The investigator has concentrated on analyzing the problems faced by the SHG members in Sivakasi. For the analysis, the investigator has used primary as well as secondary data. The sample respondents are 110 which have been selected by using proportionate stratified random sampling method. The researcher has suggested Government of India and the banks to take crucial measures to overcome certain problems faced by the SHG members.[1]